Giá trị của a^3+b^3+c^3 thỏa mãn a+b+c=0 và abc=-2

Question

Giá trị của a^3+b^3+c^3 thỏa mãn a+b+c=0 và abc=-2

in progress 0
Piper 3 tuần 2021-07-08T20:21:27+00:00 2 Answers 3 views 0

Answers ( )

    0
    2021-07-08T20:22:36+00:00

    Đáp án:

    $a^3 + b^3 + c^3 = – 6$

    Giải thích các bước giải:

    Ta có:

    $a^3 + b^3 + c^3 – 3abc$

    $= (a + b)^3 – 3ab(a + b) – 3abc + c^3$

    $= (a + b + c)[(a + b)^2 – (a + b).c + c^2] – 3ab(a + b + c)$

    $= (a + b + c)(a^2 + b^2 + c^2 – ab – bc – ca)$

    Do đó:

    $a^3 + b^3 + c^3 – 3abc = (a + b + c)(a^2 + b^2 + c^2 – ab – bc – ca)$

    Ta được:

    $a^3 + b^3 + c^3 – 3.(-2) = 0.(a^2 + b^2 + c^2 – ab – bc – ca)$

    $\Leftrightarrow a^3 + b^3 + c^3 = – 6$

    0
    2021-07-08T20:22:54+00:00

    Đáp án:

    `a^3 +b^3+ c^3 `

    ` = a^3 + ab^2 +ac^2 – a^2b – abc – a^c + a^2b + b^3 + bc^2 – ab^2 – b^2c – abc`

    ` + a^2c + b^2c + c^3 -abc – bc^2 – ac^2 + 3abc`

    ` = a(a^2 + b^2 +c^2 – ab – bc – ac) + b(a^2+ b^2 +c^2 – ab – bc – ac) + c(a^2+ b^2 +c^2 – ab – bc – ac)`

    ` + 3abc`

    `= (a+b+c)(a^2+b^2+c^2-ab-bc-ac) + 3abc`

    ` = 0* (a^2+b^2+c^2-ab-bc-ac)  + 3. (-2)`

    ` = 0  -6`

    ` = -6`

     

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )